Smoking cessation problem-based learning: Virtual experience - Ismail, Soraya; Nik Mohamed, Mohamad Haniki (2022)
Background and Objectives: Problem-based learning (PBL) is a student-centered teaching and learning methodology where students collaboratively address specific issues. Tobacco use is a major health issue globally. Health professions and students need to have knowledge and skills to facilitate smoking cessation. The objective of this study is to assess feasibility of PBL during a virtual attachment involving institutions from Malaysia and the USA.